User experience of freshmen in a private university library in Nigeria (2017)
The library as an amenity is crucial in the existence o f any academic community which is used by students, faculty members and sometimes the general public. Their use or lack o f use o f the information resources is a concern. The user experience (Ux) of freshmen (called the FALCON set) in the Igbinedion University Okada (IUO) Library, Nigeria is the focus of this study in which the survey method o f research was used. The objectives were to find out the information needs, library services experienced, services expected from the library and elicit from them suggestions for improvement o f the services. Questionnaire and observation methods were used in gathering information from four hundred and fifty (450) freshmen who took the Use o f Library, Study Skills and Information and Communication Technology (GST 121) course in the 2016/2017 session. Analysis was done using descriptive statistical measures such as frequency counts and percentages and findings were thematically discussed. Results showed that the user experiences differed and most information needs o f the freshmen were perceived to be met more by textbooks and journals as information sources over colleagues, University newsletters and the library, computer, photocopying and readers' services were mostly used. The freshmen expected gaming facilities and also a Learning Commons where they could use augmented and virtual reality for their studies. Recommendations were made for the services o f the IUO Library to be more improved to meet the new emerging technology needs o f the students and faculty.